2019
DOI: 10.3390/ani9050199
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sea and Road Transport on Physiological and Electroencephalographic Responses in Brahman Crossbred Heifers

Abstract: The objective of the current study was to evaluate the effects of sea and road transport on the acute phase proteins (APP), cortisol, metabolic, haematological and electroencephalographic (EEG) responses of Brahman crossbred heifers. Sixty Brahman crossbred heifers were subjected to 14 d of transportation by sea from Darwin Port, Australia, to Pasir Gudang Port, Johor, Malaysia, and 330 km of road transportation. Results revealed that the intensity of response for most blood biochemical parameters increased si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 70 publications
1
13
2
Order By: Relevance
“…At the point of neck cut, cortisol levels elevate further (threefold) with a mean value of 157.54 ng/mL, which may be associated with fear and novelty, stress due to handling while inside the restraint box and noise from hydraulics, as observed by numerous findings. The results observed are in line with those of elevated cortisol after long haul periods reported by Knowles and Warriss [47] and post-road transportation in cattle by Zulkifli et al [31].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…At the point of neck cut, cortisol levels elevate further (threefold) with a mean value of 157.54 ng/mL, which may be associated with fear and novelty, stress due to handling while inside the restraint box and noise from hydraulics, as observed by numerous findings. The results observed are in line with those of elevated cortisol after long haul periods reported by Knowles and Warriss [47] and post-road transportation in cattle by Zulkifli et al [31].…”
Section: Discussionsupporting
confidence: 92%
“…Data on the influence of distances and stocking density during road transportation in cattle, especially under hot, humid tropical conditions in Malaysia, are scarce. The exception to this are the most recent studies, which studied the effect of sea and road transport of farm animals [31]. These call for a study to assess the impact of road transport on farm animals, the use of which is on the rise due to high demand and the welfare problems associated with handling and thermal extremes.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that stress can exacerbate respiratory hyperreactivity and inflammation in an animal model of allergic bronchial asthma ( Joachim et al., 2003 ). Newly weaned calves experience huge stress during transportation or shipping, especially for a long distance ( Zulkifli et al., 2019 ; Malmuthuge et al., 2021 ), which may cause unclear changes in the airway for Mycoplasma proliferation. Keeping microbial balances in bovine airway during transportation might be an alternative strategy to decrease BRD morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…The sudden separation from the herd could have caused increased arousal (Briefer et al, 2015;Winblad von Walter, 2010), because physical and visual separation from the herd can cause substantial fear and anxiety response in gregarious animals like goats (Forkman et al, 2007). In previous animal slaughter studies, the increase in F 50 was suggested to be associated with nociceptive output from neck-cuts (Sabow et al, 2019;Zulkifli et al, 2014). The pre-slaughter stress may have affected the pain threshold at postslaughter in our study, because the post-S F 50 values in all lairage groups did not differ from those at pre-lairage.…”
Section: Discussionmentioning
confidence: 99%